Pengembangan Media Pembelajaran Berbasis ClassRoom Pada Mata Pelajaran Kelistrikan Otomotif: Development Of Classroom-Based Learning Media in Automotive Electricity Subjects For Class XI Automotive Engineering At Tamansiswa State High School - wahyu agung priyambodo; arif bintoro johan; suparmin suparmin (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
This type of research is development. The development model used is the four D which consists of define, design, development, and dissemination. This research was conducted at SMK Tamansiswa Nanggulan Kulon Progo with the research subjects of class XI students of Automotive Engineering. The data collection technique was carried out using a questionnaire. The data analysis technique used is descriptive data analysis technique. This learning media application can be downloaded via Google Playstore with the name Classroom on Android, iPhone, and Windows systems. The results of the feasibility assessment of classroom-based learning media by material experts obtained an eligibility percentage of 77.88% with the category